Preoperative absolute neutrophil count: a potential indicator for prognosis in carcinoembryonic antigen normal stage I non-small cell lung cancer - Wang, Bailin; Liu, Long; Cui, Meiqi; Ye, Qianwen; Li, Panhua; Yan, Bing (Frontiers in Oncology, 2025)
BackgroundCarcinoembryonic antigen (CEA) is still the most valuable tumor marker in the diagnosis and prognosis of non-small cell lung cancer (NSCLC) patients; however, its application is largely limited by its low sensitivity in stage I cases. Research on reliable and highly cost-effective prognostic indicators in CEA normal stage I NSCLC is still needed.MethodsA retrospective study was conducted in CEA normal stage I NSCLC patients. The prognostic value of peripheral blood cell fractions, including the absolute neutrophil count (ANC), was tested, and the differences in clinical features among the ANC-low or ANC-high subgroups were checked. The disease-free survival (DFS) and overall survival (OS) differences in these subgroups were run by Kaplan–Meier analysis, and the risk factors for survival were validated by a Cox proportional hazards model.ResultsAmong the tested peripheral blood cell fractions, only ANC was found to be a significant factor in predicting DFS (P = 0.011) and OS (P=0.043). The ANC displayed a positive correlation with other fractions, including the absolute lymphocyte count (R=0.26, P<0.001), absolute monocyte count (R=0.56, P<0.001), and platelet count (R=0.29, P<0.001). With a cutoff at 3879/mm3, 83.72% (252/301) of patients were divided into ANC-low and 16.28% (49/301) into ANC-high. Patients in the ANC-low group also presented a superior DFS (log rank=8.64, P = 0.003) and OS (log rank=9.86, P = 0.002) than those in the ANC-high group; however, the ANC level was not validated as an independent prognostic factor for both DFS and OS.ConclusionCompared to other peripheral blood cell fractions, preoperative ANC was found to be a useful prognostic indicator in CEA normal stage I NSCLC; however, it was not validated as an independent prognostic factor and additional studies for its role in prognosis for these patients are still needed in future.